Dependence of Si-29 NMR chemical shielding properties of precursor silicate species, Q(0) on its local structure at the pre-nucleation stages of zeolite synthesis - a DFT based computational correlation - Selvaraj, Kaliaperumal; Kurian, Reshmi (Microporous and Mesoporous Materials, 2009)
The exploration for new zeolite structures with tailored framework architectures for enhanced catalytic applications requires the knowledge about their nucleation and crystallization at molecular level. Nuclear magnetic resonance (NMR) is one of the most widely tried techniques to understand this. However, by NMR, it is difficult to accurately assign the molecular level precursor silicate structures at the pre-nucleation stages of zeolite synthesis. Hence, understanding the chemical shielding of such precursor molecules using quantum mechanical (QM) computations is extremely useful. Alkali is a fundamental component in the alkali based hydrothermal zeolite synthesis and its nature plays a major role. In the present report, we attempt to understand the differences in the local structure of the primary building block such as Si(OH)(4) (Q(0) silicate species) due to the associated alkali and their influence on NMR chemical shielding properties. Present work reports the calculation of Si-29 NMIR isotropic chemical shifts of T species with different cations such as Na, K and Ca using density functional theory (DFT). Results of natural bonding orbital (NBO) analysis, Perturbation theory energy analysis and electron density iso-surfaces were employed to obtain a deeper insight about their influence on the chemical shielding and on zeolite synthesis. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Ab initio method; Density Functional Theory (DFT); Electron density; NBO analysis; Perturbation theory; Q(0) silicate species; Si-29 NMR chemical shift; synthesis; zeolite

Defluoridation using biomimetically synthesized nano zirconium chitosan composite: kinetic and equilibrium studies - Prasad, Kumar Suranjit; Amin, Yesha; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2014)
{The present study reports a novel approach for synthesis of Zr nanoparticles using aqueous extract of Aloe vera. Resulting nanoparticles were embedded into chitosan biopolymer and termed as CNZr composite. The composite was subjected to detailed adsorption studies for removal of fluoride from aqueous solution. The synthesized Zr nanoparticles showed UV-vis absorption peak at 420 nm. TEM result showed the formation of polydispersed, nanoparticles ranging from 18 nm to 42 nm. SAED and XRD analysis suggested an fcc (face centered cubic) Zr crystallites. EDAX analysis suggested that Zr was an integral component of synthesized nanoparticles. FT-IR study indicated that functional group like -NH
Keywords: Aloe vera; Chitosan; FT-IR spectroscopy; Sorption; Zirconium nanoparticles

DFT based assay for tailor-made terpyridine ligand-metal complexation properties - Joshi, Krati; Krishnamurty, Sailaja; Singh, Iksha; Selvaraj, Kaliaperumal (Molecular Simulations, 2016)
Electron-rich terpyridine ligand and its metal complexes have a potential to grow as responsive surfaces by adapting their physicochemical properties as a function of environment. The responsiveness is brought about by judicious molecular level designing that is currently hindered due to lack of information and control on terpyridine (TPy)-metal (M) interactions at single molecule level. So far there is no organised understanding on the binding of different metals with TPy ligand and ways to modulate it. Being a large conjugated [GRAPHICS] system, TPy has a large scope to be functionalised with electron exchanging groups to alter its electronic structure and consequently its binding with metal atoms. In first report of such a kind, using density functional theory (DFT), we demonstrate that convenient modulation of TPy-M binding is possible through functionalisation of TPy for [GRAPHICS] , Ru, Fe, Mo and Au. Electron donating groups viz., CH [GRAPHICS] , OCH [GRAPHICS] , C [GRAPHICS] H [GRAPHICS] , NH [GRAPHICS] and electron withdrawing groups viz., CF [GRAPHICS] , COOH, CN and NO [GRAPHICS] are considered for functionalisation of TPy ligand. Significantly, the present work focuses on the functionalisation at 4 and 4 [GRAPHICS] positions of TPy molecule. The role of such a functionalisation in influencing the ligands structure-property correlation is missing in the literature to the best of our knowledge. The present investigation quantifies that by pertinent functionalisation of TPy, TPy-M binding energies can be modified up to [GRAPHICS] 60kcal/mol. Our results reveal that functionalisation leads to a considerable charge redistribution within the TPy-M complex with carbon atoms in pyridine rings functioning as major electron sink/source with a corresponding red/blue shift of [GRAPHICS] stretching frequency. This modifies the red-ox, optical and other chemical properties of TPy-M complexes. In brief, the present report illustrates a way to design ligands such as TPy for diverse applications through tailor-made functionalisation using electronic structure methodology.
Keywords: Binding energy; charge redistribution; Density functional theory; functionalisation; Metal organic complexes; metal-ligand interactions; terpyridine

Disintegrable NIR light triggered gold nanorods supported liposomal nanohybrids for cancer theranostics - Chauhan, Deepak S.; Prasad, Rajendra; Devrukhkar, Janhavi; Selvaraj, Kaliaperumal; Srivastava, Rohit (Bioconjugate Chemistry, 2018)
In this work, facile synthesis and application of targeted, dual therapeutic gold nanorods-liposome (GNR-Lipos) nanohybrid for imaging guided photothermal therapy and chemotherapy is investigated. The dual therapeutic GNR-Lipos nanohybrid consists of GNR supported, and doxorubicin (DOX) loaded liposome. GNRs not only serve as a photothermal agent and increase the drug release in intracellular environment of cancer cells, but also provide mechanical strength to liposomes by being decorated both inside and outside of bilayer surfaces. The designed nanohybrid shows a remarkable response for synergistic chemophotothermal therapy compared to only chemotherapy or photothermal therapy. The NIR response, efficient uptake by the cells, disintegration of GNR-Lipos nanohybrid, and synergistic therapeutic effect of photothermal and chemotherapy over breast cancer cells MDA-MB-231 are studied for the better development of a biocompatible nanomaterial based multifunctional cancer theranostic agent.

Dinitrogen activation on graphene anchored single atom catalysts: local site activity or surface phenomena - Maibam, Ashakiran; Govindaraja, Thillai; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2019)
Catalysis on two-dimensional (2D) substrates with metal clusters or centers is generally dealt with as a surface phenomenon under the conjecture that the delocalized electron density is the driving force. When single atom catalysts (SACs) are anchored on such materials with delocalized electron density, for instance graphene, the stimulant for catalysis may be either the d-electrons on the metal or the system altogether. To understand the contributing factors of catalysis on such systems, a case study of dinitrogen (N-2) activation on Mo anchored graphene has been made by employing periodic and finite models of graphene. The periodic model represents a continuum of SACs anchored periodically on graphene, while the finite models are graphene nanoflakes of varying sizes and edge orientations. In addition to the physical aspects, such as size/finiteness of graphene, the influence of varying chemical compositions of the substrate on the activity is also evaluated by doping graphene with different B and N concentrations. This study, while clearly bringing out the connotation of regulating atomic composition of graphene substrate for dinitrogen activation, also surprisingly unveils the relative insignificance of varying the size and edge effects of the substrate. These features are highlighted through an analysis of red shift in the N-N stretching frequency, charge transfer to dinitrogen from the catalytic system, and structural and electronic characteristics of the catalytic system. The total and projected density of states plots reveal hybridization between the metal d orbitals and the p orbitals of carbon and nitrogen in the valence band. On the other hand, the frontier molecular orbital analysis also depicts a strong chemisorption of dinitrogen with the metal-graphene supports on account of direct hybridization between the d orbitals of the supported metal atom and the p orbitals of dinitrogen. The Bader and Lowdin charge distribution on the adsorbed dinitrogen in periodic and finite models shows the preeminence of local site over the surface activity.